2021
DOI: 10.1093/milmed/usab043
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Functional Motor Competence to Promote Physical Military Readiness: A Developmental Perspective

Abstract: Decreased physical fitness in military recruiting populations is problematic for the development of physical military readiness (PMR) and presents a threat to national security. The demonstration of low levels of fitness may be an indicator of a more foundational problem in the physical development of military recruits. We propose the development of functional motor competence (FMC) across childhood and adolescence as a necessary antecedent to advanced PMR training and military-specific tasks (i.e., rucking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…At the same time, a key role in expert performance is noted by eye-hand coordination, multijoint coordination, perceptuomotor coordination, and speed of movement [3,[10][11][12][13][14]. These capabilities are inherently demonstrated in the assessment of Functional Motor Competence (FMC) skills and are key elements of the perceptuomotor integration process needed to perform goal-direct movements [15][16][17]. Previous studies suggested addressing how several performance-related factors (e.g., MSF and FMC), together as a multicomponent concept (i.e., Functional Fitness), impact on talent identification in sport [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a key role in expert performance is noted by eye-hand coordination, multijoint coordination, perceptuomotor coordination, and speed of movement [3,[10][11][12][13][14]. These capabilities are inherently demonstrated in the assessment of Functional Motor Competence (FMC) skills and are key elements of the perceptuomotor integration process needed to perform goal-direct movements [15][16][17]. Previous studies suggested addressing how several performance-related factors (e.g., MSF and FMC), together as a multicomponent concept (i.e., Functional Fitness), impact on talent identification in sport [18,19].…”
Section: Introductionmentioning
confidence: 99%